Analysis of the situation of fish farming in the state of Pará, Brazil (Research, Society and Development, 2023)
Pisciculture is the area of aquaculture that deals with the production of fish in captivity. With the projected population growth, the demand for food tends to grow dramatically, and fish protein is an important source to promote food security. Knowing the environment of an activity is of paramount importance for decision making. The conjuncture analysis is a frequently used tool to characterize the state of the art of an activity. Therefore, the objective of this work is to evaluate the situation of fish farming in the state of Pará. Secondary data were collected on the IBGE's SIDRA platform, and graphs and tables were then created. Nationally, tilapia is the most produced species in captivity, and its production has been increasing progressively. The tambaqui, in second place, presents constant production. The South region, with emphasis on the state of Paraná, has the highest fish production in the country, followed by the Northeast, while the North occupies the fourth place, with indications of productive decrease. Paragominas is the municipality of Pará with the highest production, along with Marabá and Conceição do Araguaia, located in Southeast Pará. Regional production is focused on the production of tambaqui and its hybrids, which comprise most of the production. There is a downward trend in production for tambaqui in the state of Pará. Tilapia is little produced and tends to keep its production stagnant. The advance in the research of fish farming in Pará is of paramount importance for its development.